Georg Simmel as unrecognized media ecologist. Issue 3 (1st December 2013) - Anton, Corey
This article considers Georg Simmel's contributions to media ecology. By examining various dialectics of subjectivity and cultural form (especially how valuation relates to money) and also by delineating how humanity takes its structure from resistances and boundaries which in their turn need to be transcended, Simmel's work outlines both the basic dynamics of cultural process and the tragedy of culture itself: people can grow themselves only by fashioning and cultivating the world, and yet, as civilization grows, people increasingly shape themselves by beginning their worldly pursuits in the trails that others have left behind. An unfortunate consequence is that many cultural forms and practices quite easily become understood as wholly ends in themselves rather than as they were originally understood, means to an end.